Antibiofilm efficacy of a calcium silicate-based intracanal medicament against Fusobacterium nucleatum strains - Hanan Balto; Reem Barakat; Sumaya Basudan; Ghazal Fakeeha; Sarah R. Alharbi; Rahaf Almohareb (Scientific Reports)
Abstract This study evaluated the antibiofilm efficacy of a calcium silicate-based intracanal medicament (Bio-C Temp) against Fusobacterium nucleatum (F. nucleatum). Dentin slices (n = 88) were inoculated with F. nucleatum biofilms and divided into experimental groups (n = 24 each) treated with Bio-C Temp, triple antibiotic paste (TAP), or Ca(OH)2 for 1 or 2 weeks. Untreated dentin slices exposed to saline served as a positive control, while sterile dentin slices incubated anaerobically served as a negative control. Bacterial viability was assessed using confocal laser scanning microscopy after staining with LIVE/DEAD® BacLight™ dye. Samples treated with TAP demonstrated the highest percentage of dead bacteria (95%). The antibiofilm effect of TAP and Bio-C Temp significantly increased from Week 1 to Week 2. At Week 2, samples treated with Bio-C Temp showed a significantly higher percentage of dead bacteria (75.25%) than those treated with Ca(OH)2 (58.65%). TAP showed superior efficacy against F. nucleatum biofilms. After an application time of 2 weeks, the antibiofilm efficacy of Bio-C Temp was superior to that of Ca(OH)2.